Evaluation of Extensions of Sinonasal Malignancy by Clinical, Surgical & CT Scan Findings (Bangladesh Journal of Otorhinolaryngology, 2023)
Background: Sinonasal malignancies are challenging not only from diagnostic view point but also from therapeutic aspects. Owing to the rarity of the lesions, delayed clinical presentations and poor prognosis there is lack of large experience.Objectives: Aim of this study is to assess Evaluation of extensions of sinonasal malignancy by correlating clinical and surgical findings with CT scan.Methods: A Cross Sectional study was carried out in the Department of Otolaryngology-Head and Neck Surgery, Sylhet M.A.G Osmani Medical College Hospital, Sylhet, from August 2019 to July 2021. A total 30 subjects were included in this study based on inclusion and exclusion criteria. A data collection form was designed and prepared including general characteristics of subjects and reviewed clinically, radiologically and surgically. All the data were compiled and sorted properly and the numerical data were analyzed statistically by using Statistical Package for Social Sciences (SPSS-26). The result was expressed as frequency and percentage and displayed with figure and table. Z proportion test, Spearman’s rho correlation coefficient test and Diagnostic accuracy test of clinical, CT and surgical finding were performed as applicable. For all comparisons p value of